MOLECULAR DOCKING STUDIES OF RICINUS COMMUNIS PHYTOCHEMICALS AGAINST BETA-LACTAMASE FROM ENTEROCOCCUS FAECALIS AND STAPHYLOCOCCUS AUREUS - Umaarasu, Thirunavukkarasu; Padmavathy, Kesavaram; Thirunavukkarasu, Dharmalingam; Sv, Rajesh; Shanmugam, Gnanendra (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Objective: The objective of this study is to investigate the antibacterial activity of Ricinus communis phytochemicals against beta-lactamase from Enterococcus faecalis and Staphylococcus aureus through molecular docking studies. Methods: The three-dimensional (3D) structure of beta-lactamase from E. faecalis was modeled using modeler 9v9 and validated. The 3D structure of beta-lactamase from S. aureus (PDB ID: 1 GHP) was retrieved from PDB database. The 2D structures of 29 phytochemical compounds from the methanol leaf extracts of R. communis were drawn in ACD-Chemsketch and converted into 3D structures. The 3D structure of R. communis leaf compounds and cefotaxime (control) was virtually screened in the binding pockets of Î²-lactamase proteins from E. faecalis and S. aureus using FlexX docking program. Results: The docking studies revealed that ferulic acid and hyperoside exhibited promising minimum binding and docking energy that is closely related to the docking score of standard antibiotic cefotaxime. Conclusion: The result of the present study indicates that ferulic acid and hyperoside are potential compounds that could be effectively used in the treatment of infections caused by E. faecalis and S. aureus. However, further clinical studies are required to ascertain the antibacterial activity and potential toxic effects of ferulic acid and hyperoside in vivo.Â 